2021
DOI: 10.1007/s13304-021-01085-5
|View full text |Cite
|
Sign up to set email alerts
|

A predictive score for 30-day survival for patients undergoing major lower limb amputation for peripheral arterial obstructive disease

Abstract: To analyze outcomes following major lower extremity amputations (mLEAs) for peripheral arterial obstructive disease, gangrene, infected non-healing wound and to create a risk prediction scoring system for 30-day mortality. In this single-center, retrospective, observational cohort study. All patients treated with above-the-knee amputation (AKA) or below-the-knee amputation (BKA) between January 1st, 2010 and June 30th, 2018 were identified. The primary outcome of interest was early (≤ 30 days) mortality. Secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…The largest improvement in discrimination was in a tool predicting mortality following AKA (from 0.789 to 0.827). 29 There remained significant lack of fit when testing calibration (apart from 5 tools), 1,[24][25][26][27] the tendency to under/overestimate risk was unchanged, and Brier scores were comparable to the primary analyses (Supplementary material 2).…”
Section: Covid-19mentioning
confidence: 97%
See 1 more Smart Citation
“…The largest improvement in discrimination was in a tool predicting mortality following AKA (from 0.789 to 0.827). 29 There remained significant lack of fit when testing calibration (apart from 5 tools), 1,[24][25][26][27] the tendency to under/overestimate risk was unchanged, and Brier scores were comparable to the primary analyses (Supplementary material 2).…”
Section: Covid-19mentioning
confidence: 97%
“…Following title and abstract screening (n=421) and full-text screening (n=5) in the updated systematic search, two further tools described in two papers were identified for evaluation (both predicting mortality at 30-days). 24,25 Following the conclusion of the initial phase of the study, a further two outcome prediction tools were found to be of interest in the context of the PERCEIVE study despite not being specific to MLLA: version 1 and version 2 of the Surgical Outcome Risk Tool (SORT). 26,27 SORT version 1 is a 'traditional' regression-based outcome prediction tool; SORT version 2 incorporates clinician subjective estimation in the regression equation and was, therefore, considered relevant to this study.…”
Section: Existing Outcome Prediction Tools Identificationmentioning
confidence: 99%
“…However, even in a modern series for primary major amputation in CLTI patients, 30 day mortality was reported to be between 10.8% for the lower-risk score and 28.7% for the higher-risk score patients. [33] With respect to the poor prognosis for primary amputation, a surgical revascularization approach may be discussed in this high-surgical-risk group with no good endovascular option to preserve patient mobility with a functional limb besides a strict conservative management. The SCBB developed by Deutsch is associated with good late bypass patency and an excel-lent limb salvage rate if performed with a heparin-bonded PTFE-prosthesis.…”
Section: Discussionmentioning
confidence: 99%